Impact performance of low cement Ultra-high-performance concrete - Azmee, N.M. (WITPress, 2017)
Technology advancement in concrete industry and expanding interest for high quality construction materials have prompted the development of Ultra-High-Performance Concrete (UHPC). Despite of many advantages gained using UHPC, however, conventional design of UHPC poses many concerns especially on sustainability issues. Producing UHPC, requires relatively high amount of cement content and in most cases, the compositions are not optimized causing an increase in materials and energy cost. Low cement UHPC was proposed to minimize the economic and environmental disadvantages of current UHPC by incorporating high volume of Fly Ash (FA) and Silica Fume (SF) as cement replacement materials and locally available coarse aggregates. An experimental program was carried out to evaluate the effect of combined FA and SF on mechanical and impact performance of low cement UHPC. Both hooked and straight steel fibers with aspect ratio of 83 and 100 were used respectively as the reinforcing material. An enhancement of 111 was observed in impact resistance of the fibrous concretes with an incorporation of both FA and SF replacing 50 of cement, as compared to specimen without any replacement. © 2017 WIT Press.